Eye Bank Management of Irregular Descemet Stripping Automated Endothelial Keratoplasty Lenticules. Issue 6 (June 2021) - Ruzza, Alessandro; Galeone, Alessandra; Baruzzo, Mattia; Favaro, Elisa; Parekh, Mohit; Ferrari, Stefano; Ponzin, Diego
Abstract : Purpose: To report the management of precut Descemet stripping automated endothelial keratoplasty (DSAEK) lenticules unsuitable for transplantation because of irregular anterior profile after microkeratome cutting. Methods: After preparation for DSAEK, 20 tissues were considered unsuitable for transplantation because of nonhomogeneous posterior stromal thickness. To convert them into suitable tissues for surgery, manual stromal delamination was performed by removing the excess stromal layers after the indications obtained through optical coherence tomography. These tissues were further transplanted as ultrathin DSAEK. Results: Nineteen tissues were delaminated successfully. The average reduction in thickness in the center (63 ± 69 μm; P = 0.0101) and periphery (129 ± 39 μm; P < 0.0001) before and after delamination was significantly different. One tissue showed signs of perforation during manual dissection and therefore considered unsuitable for transplantation. Primary graft failure was reported in one case, but it was not correlated with the tissue preparation. No other clinical complications were observed after surgery. Conclusions: Manual delamination of the stroma because of irregular microkeratome cutting is a viable option to obtain a uniform graft thickness required for DSAEK surgeries. This technique can further reduce tissue wastage that is observed after microkeratome cutting errors. Abstract : Supplemental Digital Content is Available in the Text.